Performance Comparison between Classic and Intelligent Methods for Position Control of DC Motor - Navid Moshtaghi Yazdani; Arezoo Yazdani Seqerloo (Institute of Advanced Engineering and Science, 2014)
Controlling DC motors is mainly done by controlling either voltage or field of their armature. Numerous methods have been proposed so far for this purpose. Some intelligent methods such as XCSR and machine learning systems are used to control position of a separately excited DC motor. Having set output position of the motor to its basic position, voltage of armature becomes zero and the motor stops working. Characteristic features of the methods in this paper are resistance against changing friction and moment of inertia. Meanwhile, time to reach stability in this type of controllers is considerably lower than that of PID controller with no oscillations being observed in the responses.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5355